The Effect of Life History on Alopias pelagicus Overexploitation Vulnerability: A Literature Review - Hewindati, Yuni Tri; Novita Sari, Dhian (Leuser Journal of Environmental Studies, 2023)
Alopias pelagicus Nakamura 1935 or pelagic thresher shark is an epipelagic species of shark prone to overexploitation due to its epipelagic habitat and slow life history. In 2019, based on existing data on abundance and exploitation, A. Pelagicus was included in the International Union for Conservation of Nature (IUCN) Red List of Threatened Species with the category of endangered (EN). This literature review analyzed the relationship between A. pelagicus life history and overexploitation susceptibility. The method used is a comprehensive search of international journals in online databases from ScienceDirect and Google Scholar with certain inclusion and exclusion criteria. Based on the criteria, seven out of 270 search results of international journal articles were included for the analysis. The results from the seven journal articles shows that A. pelagicus has a slow life history or k-selected life history. This life history is characterized by slow sexual maturity, low fecundity, long gestation period, annual reproductive cycle, slow growth, long lifespan, and low natural mortality rate. This life history makes A. pelagicus prone to overexploitation because if the mortality rate of catching exceeds the natural mortality rate, it will take a long time for A. pelagicus to return to their original population size.